Study guides

☆☆

Q: X2 plus 26x plus

Write your answer...

Submit

Still have questions?

Related questions

x2 + 26x + 48 = (x + 24)(x + 2)

x2+36x+120 (x+6)(x+20)

x2+26x = 68 x2+26x-68 = 0 (x+13)2-68 = 0 (x+13)2-169-68 = 0 x+13 = +/- the square root of 237 x = -13 +/- the square root of 237

x2 + x2 + x2 = (1 + 1 + 1)x2 = 3x2

x2 + x2 = 2x2

x2+26x = 68 Completing the square: (x+13)2-169-68 = 0 (x+13)2-237 = 0 x+13 = -/+ sq rt 237 x = -13-/+ sq rt 237

x2 + x2 = 2x2

3x4 plus 5x3 plus x2 - 5 divided by x 2 =[(3x4) + (5x3) + (x2 - 5)]/x2 =(12 + 15 + x2 -5)/x2 =(27 - 5 + x2)/x2 =(22 + x2)/x2

x2 + 48x + 320

x2 + 48x + 320

2x4 - 26x2 + 72 = 0Divide each side by 2:x4 - 13x2 + 36 = 0(x2 - 9) (x2 - 4) = 0A). x2 - 9 = 0B). x2 - 4 = 0______________________A). (x + 3) (x - 3) = 0x = +3x = -3B). (x + 4) (x - 4) = 0x = +4x = -4

4x2 + x2 = 8 + x2

People also asked